The effect of liquidity and monetary policy on bank credit distribution - Romadhan, Rifki (Privietlab, 2026)
This study examines the influence of deposit interest rates, lending rates, Non-Performing Loans (NPL), inflation, and broad money (M2) on bank credit distribution in Indonesia. Using monthly data from September 2016 to June 2025 and employing a multiple linear regression framework complemented by an Indicator Saturation approach to detect and control outliers and structural shocks, this research provides empirical insights into the macroeconomic and systemic risk determinants of banking intermediation. The estimation results show that deposit interest rates and M2 exert a positive and significant impact on bank credit, while lending rates, inflation, and NPL have significant negative effects. The model demonstrates strong explanatory power, indicated by an R-squared value of 0.987, and satisfies the classical assumption tests, including normality, absence of excessive multicollinearity, and no evidence of autocorrelation or heteroskedasticity. These findings highlight the importance of liquidity conditions, asset quality, and monetary stability in sustaining credit distribution within the banking sector. Future research is encouraged to incorporate dynamic modeling techniques and additional micro-banking indicators to achieve a more comprehensive understanding of the factors influencing banking intermediation in Indonesia.